Vertical monolithic integration of wide- and narrow-bandgap semiconductor nanostructures on graphene films - Tchoe, Youngbin; Jo, Janghyun; Kim, HoSung; Kim, Heehun; Baek, Hyeonjun; Lee, Keundong; Yoo, Dongha; Choi, Won Jun; Kim, Miyoung; Yi, Gyu-Chul (NATURE RESEARCH, 2021)
We report monolithic integration of indium arsenide (InAs) nanorods and zinc oxide (ZnO) nanotubes using a multilayer graphene film as a suspended substrate, and the fabrication of dual-wavelength photodetectors with the hybrid configuration of these materials. For the hybrid nanostructures, ZnO nanotubes and InAs nanorods were grown vertically on the top and bottom surfaces of the graphene films by metal-organic vapor-phase epitaxy and molecular beam epitaxy, respectively. The structural, optical, and electrical characteristics of the hybrid nanostructures were investigated using transmission electron microscopy, spectral photoresponse analysis, and current-voltage measurements. Furthermore, the hybrid nanostructures were used to fabricate dual-wavelength photodetectors sensitive to both ultraviolet and mid-infrared wavelengths.
Keywords: NANOWIRES; GROWTH; PHOTODETECTORS